Microscale tissue engineering of liver lobule models: advancements and applications - Wang, Qi; Liu, Juan; Yin, Wenzhen; Wang, Anqi; Zheng, Jingjing; Wang, Yunfang; Dong, Jiahong (Frontiers in Bioengineering and Biotechnology, 2023)
The liver, as the body's primary organ for maintaining internal balance, is composed of numerous hexagonal liver lobules, each sharing a uniform architectural framework. These liver lobules serve as the basic structural and functional units of the liver, comprised of central veins, hepatic plates, hepatic sinusoids, and minute bile ducts. Meanwhile, within liver lobules, distinct regions of hepatocytes carry out diverse functions. The in vitro construction of liver lobule models, faithfully replicating their structure and function, holds paramount significance for research in liver development and diseases. This is a provisional file, not the final typeset article Presently, two primary technologies for constructing liver lobule models dominate the field: 3D bioprinting and microfluidic techniques. 3D bioprinting enables precise deposition of cells and biomaterials, while microfluidics facilitates targeted transport of cells or other culture materials to specified locations, effectively managing culture media input and output through micro-pump control, enabling dynamic simulations of liver lobules. In this comprehensive review, we provide an overview of the biomaterials, cells, and manufacturing methods employed by recent researchers in constructing liver lobule models. Our aim is to explore strategies and technologies that closely emulate the authentic structure and function of liver lobules, offering invaluable insights for research into liver diseases, drug screening, drug toxicity assessment, and cell replacement therapy.